Low-temperature early-strength low-density cement-based material for deepwater well cementation and preparation method thereof
By using low-temperature early strength low-density cement based materials in deep water cementing, combined with the ratio and process processing of G-grade oil well cement, ultrafine silicate cement, active materials and density-adjusting materials, the problems of slow hydration of low-temperature cement and thickening of early strength agents are solved, and the early strength of cement is significantly improved and the construction performance optimization is achieved.
Patent Information
- Application Number
- CN202411858331.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The cement hydration of deep water cement wells is slow in low temperature environments, resulting in insufficient development of cement stone strength, increasing the risk of annular flow. The existing premature strengthening agents have thickening problems, affecting construction performance.
Low-temperature early strength low-density cement-based materials, including mixed cementitious materials of G-level oil well cement and ultrafine silicate cement, active materials of metakaolin and microsilicon, strength reinforcement materials of active components A and B, and density adjustment materials of hollow glass microbeads, and cement-based materials with good early strength and construction performance are prepared through ball milling and pneumatic mixing processes.
It significantly improves the development rate of early strength of cement, shortens the setting time of cement slurry, enhances the cementitiousness and sealing properties of cementing cement stone, reduces the risk of low-temperature shallow water and gas traversing, and has good construction performance, which is suitable for deep water cementing applications.
Smart Images

Figure BDA0005192498440000081 
Figure BDA0005192498440000091 
Figure BDA0005192498440000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil and gas resource development, and in particular to a low-temperature, early-strength, low-density cement-based material for deep-water cementing and a preparation method thereof. Background Art
[0002] As the focus of oil and gas exploration and production gradually shifts from land to ocean, deepwater contains rich oil and gas resources, and the research and development of deepwater oil and gas production technology is particularly important. However, deepwater cementing faces a series of problems. The hydration of oil well cement is very slow under low temperature environment, which seriously affects the development of cement stone strength and increases the risk of annular channeling. In addition, due to the characteristics of low fracture pressure, low-density cement slurry system is usually selected. At present, most of the solutions are to add early strength agents to cementing cement slurry to improve its early strength development, but most conventional early strength agents have serious thickening problems, especially the commonly used new early strength agents containing calcium ions and nanomaterials, which have a great impact on the construction performance of cement slurry.
[0003] In view of the problem of deepwater low-temperature cementing, existing research has achieved great results, but the comprehensive performance of low-temperature cementing slurry has been less considered. Therefore, a low-temperature early-strength, low-density cement-based material with fast early strength development, anti-gas channeling, and good construction performance is needed. Summary of the invention
[0004] In order to overcome the above technical difficulties, the present invention provides a low-temperature, early-strength, low-density cement-based material for deep-water cementing and a preparation method thereof.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] In one aspect, the present invention provides a low-temperature, early-strength, low-density cement-based material for deepwater cementing, comprising the following raw materials by weight percentage:
[0007] Cementitious material: 54-70wt%;
[0008] Active material: 20wt%;
[0009] Strength enhancing material: 3-6wt%;
[0010] Density adjusting material: 5-15wt%;
[0011] Fluid loss reducer: 1-3wt%;
[0012] Dispersant: 1-2wt%;
[0013] The cementitious material is a mixture of G-grade oil well cement and ultrafine silicate cement in a mass ratio of 7:3; the active material is a mixture of metakaolin and microsilica in a mass ratio of 1:1.
[0014] Furthermore, the SiO 2 The content is 48-54wt%, Al 2 O 3 The content is 40-45wt%, and the powder particle size is less than 600 mesh.
[0015] Furthermore, the SiO 2 The content is 96wt% and the particle size is 0.05-0.30μm.
[0016] Furthermore, the density adjusting material is hollow glass microspheres with a density of 0.44-0.48 g / cm 3 , median particle size is 40μm, and compressive strength is >4000psi.
[0017] Furthermore, the strength enhancing material is prepared by mixing active component A, active component B and reinforcing component in a mass ratio of 1:3:1, and the preparation method is as follows:
[0018] Sa1, mixing the active component A and the reinforcing component to obtain powder A;
[0019] Sa2, the active component B is placed in a ball mill and ball milled at a speed of 500 rpm for 6 hours to obtain powder B;
[0020] Sa3. Powder A and powder B are pneumatically mixed to obtain a strength-enhanced material.
[0021] The strength enhancing material of the present invention can provide an alkaline environment for the initial hydration reaction of cement, which can promote the hydration reaction of cement on the one hand; on the other hand, it can stimulate the activity of active component B, promote the activation and decomposition of solid waste residue in active component B, and promote the decomposition of Si 4+ 、Al 3+ and Ca 2+ Plasma release accelerates the formation of hydration products. In addition, the active component A in the present invention can act as calcium silicate hydrate and calcium aluminosilicate hydrate crystal seeds in the early stage of hydration, provide a good nucleus effect in the cement hydration process, induce the formation of calcium silicate hydrate and calcium aluminosilicate hydrate in the cement hydration process, promote cement hydration and thus improve the early strength of cement.
[0022] Furthermore, the active component A is prepared by mixing carbide slag, biomass slag and aerated concrete waste in a mass ratio of 5:4:1, and the preparation method is as follows:
[0023] Sb1, carbide slag, biomass slag and aerated concrete waste were placed in a ball mill according to a mass ratio of 5:4:1, with a liquid-to-solid ratio of 1.0, and ball milled at a speed of 400 rpm for 72 hours to obtain slurry A;
[0024] Sb2. Place slurry A in a sealed stirring tank, add 1 wt% of the solid mass of the dispersion stabilizer in slurry A and stir at 80° C. for 72 h to obtain slurry B;
[0025] Sb3, placing slurry B in a centrifugal device for liquid-solid separation, drying the solid phase at the bottom of the liquid-solid separation into dry powder to obtain active component A;
[0026] Preferably, the CaO content of the carbide slag is 65-70wt%, and the pH is 12-13; the SiO 2 Content ≥ 65wt%, Al 2 O 3 The content is ≥15wt% and the particle size is less than 325 meshes; the aerated concrete waste is composed of tobermorite, semi-crystalline CSH (I), CSH gel and silicon dioxide, and after crushing and grinding, the powder fineness is less than 600 meshes; the dispersion stabilizer is a mixture of ketone-aldehyde condensation product and microcrystalline cellulose.
[0027] The active component A of the present invention utilizes carbide slag, biomass slag and aerated concrete waste to react under wet grinding conditions to generate calcium silicate hydrate and calcium aluminosilicate hydrate. The aerated concrete waste contains a large amount of tobermorite, which can serve as a nucleation site for calcium silicate and calcium aluminosilicate hydrate, greatly accelerating the formation of calcium silicate hydrate and calcium aluminosilicate hydrate and promoting cement hydration reaction.
[0028] Furthermore, the active component B is prepared by mixing modified zirconium silicon slag, silicon manganese slag, phosphorus slag and alkaline slag in a mass ratio of 3:2:1:1, and the modified zirconium silicon slag is prepared by making slurry C from zirconium silicon slag, and the slurry C is subjected to solid-liquid separation after neutralization, water washing and impurity removal, and then high-temperature drying and grinding to obtain a product;
[0029] Preferably, the SiO of the modified zirconium-silicon slag is 2 The content is ≥90wt%, the pH is neutral, and the powder particle size is less than 325 mesh; the powder particle size of the silicon manganese slag is less than 325 mesh, SiO 2 The content is 35-40wt%, Al 2 O 3 The content of SiO in the phosphorus slag is 9-12wt%, the content of CaO is 25-28wt%, and the content of MgO is 6-11wt%; 2 The content is 35-40wt%, and the CaO content is 42-48wt%; the CaCO 3 The content is 40-45wt%, CaSO 4 The content is 7-10wt%, CaCl 2 The content is 10-14wt%.
[0030] The active component B of the present invention contains a large amount of amorphous SiO 2 Granules, highly active and can quickly react with cement hydration product Ca(OH) 2 Carry out hydration reaction to accelerate cement hydration; at the same time, active component B also contains a small amount of MgO and CaSO 4 On the one hand, it can promote the crystallization of ettringite through synergistic effect with the reinforcing components, and on the other hand, it can form Mg(OH) 2 , enhance the bonding and sealing properties of cement stone, thereby improving the anti-channeling ability of cement stone.
[0031] Furthermore, the reinforcing component is formed by mixing lithium silicate and aluminum sulfate in a mass ratio of 1:2; preferably, the purity of the lithium silicate is greater than 98wt%, and the purity of the aluminum sulfate is greater than 98wt%.
[0032] The reinforcing component of the present invention can react with free hydroxide ions (OH - ) and calcium ions (Ca 2+ ) reaction to generate silicate gel and calcium silicate, which fill the micropores and gaps of the hydration product, thereby improving the density of the matrix. The generated silicate gel and calcium silicate further promote the formation of hydrated calcium silicate and hydrated calcium aluminosilicate through synergistic reinforcement with the active component A; the reinforcement component can also promote the crystallization of ettringite together with the various ions released by the active component B. 4+ 、Al 3+ and Ca 2+ The consumption of plasma further promotes the hydration of cement and the dissociation and activity release of active component B, thereby promoting the formation of early strength. + Accelerate the destruction of the early hydration product film coated on the cement particles and speed up the hydration process; the cement hydration product Ca(OH) 2 It can also stimulate the activity of solid waste-based reinforcing materials used in cementing cement, react with them, and promote the occurrence of hydration reactions.
[0033] Furthermore, the fluid loss additive is a 2-acrylamido-2-methylpropanesulfonic acid (AMPS) / acrylamide (AM) copolymer; and the dispersant is a sulfonated acetone formaldehyde condensate.
[0034] On the other hand, the present invention provides a method for preparing a low-temperature, early-strength, low-density cement-based material for deepwater cementing, comprising: uniformly mixing a gelling material, an active material, a strength enhancing material, a density adjusting material, a fluid loss reducer and a dispersant according to respective weight ratios to form a dry powder, thereby obtaining a low-temperature, early-strength, low-density cement-based material for deepwater cementing.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] 1. The density regulating material of the present invention can achieve a density of 1.3 to 1.5 g / cm 3 The invention uses solid waste as raw material for preparation, which helps to reduce environmental pressure and has the characteristics of green environmental protection, low cost, etc.
[0037] 2. The strength enhancing material of the present invention provides an alkaline environment for the initial hydration reaction of cement, which not only promotes the hydration reaction of cement, but also stimulates the activity of active components, accelerates the dissolution of active ions, and reacts with the SO dissolved by the active components themselves. 4 2- Together they promote the formation of hydration products such as calcium aluminate. In addition, a small amount of MgO in the strength enhancing material forms Mg(OH) during cement hydration. 2 , interacting with the generated calcium aluminate, so that the cement slurry has a certain micro-expansion, synergistically enhancing the bonding and sealing properties of the cementing cement stone, thereby improving the anti-channeling ability of the cementing cement stone.
[0038] 3. The strength enhancing material of the present invention can be used as a seed of calcium silicate hydrate and calcium aluminosilicate hydrate in the early stage of hydration, and the reinforcing component can react with free hydroxide ions (OH - ) and calcium ions (Ca 2+ ) reaction to form silicate cement and calcium silicate, which provide a good nucleus effect in the cement hydration process, induce the formation of hydrated calcium silicate and hydrated calcium aluminosilicate in the cement hydration process, promote cement hydration and thus improve the early strength of cement. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0040] The following examples all prepare cement slurries according to GB / T19139 standard, wherein the G-grade oil well cement and ultrafine silicate cement are provided by Jiahua Special Cement Co., Ltd., the fluid loss reducer is AMPS / AM copolymer, and the dispersant is sulfonated acetone formaldehyde condensate.
[0041] Example 1
[0042] As a preferred embodiment of the present invention, the specific composition of the low-temperature, early-strength, low-density cement-based material for deep-water cementing in this embodiment is shown in Table 1 below:
[0043] Table 1
[0044] raw material Weight ratio (wt%) Cementitious materials 54 Active Materials 20 Strength enhancing materials 6 Density Adjustment Materials 15 Fluid Loss Additive 3 Dispersants 2
[0045] In this embodiment, the cementitious material is a mixture of G-grade oil well cement and ultrafine silicate cement in a mass ratio of 7:3.
[0046] In this embodiment, the active material is a mixture of kaolin and microsilicon in a mass ratio of 1:1.
[0047] In this embodiment, the active component A, active component B and reinforcing component of the strength enhancing material are mixed in a mass ratio of 1:3:1.
[0048] In this embodiment, the density adjustment material is hollow glass microspheres with a density of 0.44-0.48 g / cm 3 , median particle size is 40μm, and compressive strength is >4000psi.
[0049] The cementitious material, active material, strength enhancing material, density regulating material, fluid loss reducing agent and dispersant are uniformly mixed according to the weight ratio in Table 1 to form dry powder, and a low-temperature early-strength low-density cement-based material 1# for deepwater cementing is obtained.
[0050] The cement slurry was prepared according to GB / T19139 standard with a water-cement ratio of 0.6, and the cement slurry system 1# was prepared by using low-temperature, early-strength, low-density cement-based material 1# for deep water cementing.
[0051] Example 2
[0052] As a preferred embodiment of the present invention, the specific composition of the low-temperature, early-strength, low-density cement-based material for deep-water cementing in this embodiment is shown in Table 2 below:
[0053] Table 2
[0054] raw material Weight ratio (wt%) Cementitious materials 62 Active Materials 20 Strength enhancing materials 4.5 Density Adjustment Materials 10 Fluid Loss Additive 2 Dispersants 1.5
[0055] In this embodiment, the cementitious material is a mixture of G-grade oil well cement and ultrafine silicate cement in a mass ratio of 7:3.
[0056] In this embodiment, the active material is a mixture of kaolin and microsilicon in a mass ratio of 1:1.
[0057] In this embodiment, the active component A, active component B and reinforcing component of the strength enhancing material are mixed in a mass ratio of 1:3:1.
[0058] In this embodiment, the density adjustment material is hollow glass microspheres with a density of 0.44-0.48 g / cm 3 , median particle size is 40μm, and compressive strength is >4000psi.
[0059] The cementitious material, active material, strength enhancing material, density regulating material, fluid loss reducer and dispersant were uniformly mixed according to the weight ratio in Table 2 to form dry powder, and a low-temperature, early-strength, low-density cement-based material 2# for deepwater cementing was obtained.
[0060] The cement slurry was prepared according to GB / T19139 standard with a water-cement ratio of 0.6, and the cement slurry system 2# was prepared by using low-temperature, early-strength, low-density cement-based material 2# for deep water cementing.
[0061] Example 3
[0062] As a preferred embodiment of the present invention, the specific composition of the low-temperature, early-strength, low-density cement-based material for deep-water cementing in this embodiment is shown in Table 3 below:
[0063] Table 3
[0064] raw material Weight ratio (wt%) Cementitious materials 70 Active Materials 20 Strength enhancing materials 3 Density Adjustment Materials 5 Fluid Loss Additive 1 Dispersants 1
[0065] In this embodiment, the cementitious material is a mixture of G-grade oil well cement and ultrafine silicate cement in a mass ratio of 7:3.
[0066] In this embodiment, the active material is a mixture of kaolin and microsilicon in a mass ratio of 1:1.
[0067] In this embodiment, the active component A, active component B and reinforcing component of the strength enhancing material are mixed in a mass ratio of 1:3:1.
[0068] In this embodiment, the density adjustment material is hollow glass microspheres with a density of 0.44-0.48 g / cm 3 , median particle size is 40μm, and compressive strength is >4000psi.
[0069] The cementitious material, active material, strength enhancing material, density regulating material, fluid loss reducer and dispersant were uniformly mixed according to the weight ratio in Table 3 to form dry powder, and low-temperature early-strength low-density cement-based material 3# for deepwater cementing was obtained.
[0070] The cement slurry was prepared according to GB / T19139 standard with a water-cement ratio of 0.6, and the cement slurry system 3# was prepared by using low-temperature, early-strength, low-density cement-based material 3# for deep water cementing.
[0071] Example 4
[0072] As a preferred embodiment of the present invention, the specific composition of the low-temperature, early-strength, low-density cement-based material for deep-water cementing in this embodiment is shown in Table 4 below:
[0073] Table 4
[0074] raw material Weight ratio (wt%) Cementitious materials 67 Active Materials 20 Strength enhancing materials 6 Density Adjustment Materials 5 Fluid Loss Additive 1 Dispersants 1
[0075] In this embodiment, the cementitious material is a mixture of G-grade oil well cement and ultrafine silicate cement in a mass ratio of 7:3.
[0076] In this embodiment, the active material is a mixture of kaolin and microsilicon in a mass ratio of 1:1.
[0077] In this embodiment, the active component A, active component B and reinforcing component of the strength enhancing material are mixed in a mass ratio of 1:3:1.
[0078] In this embodiment, the density adjustment material is hollow glass microspheres with a density of 0.44-0.48 g / cm 3 , median particle size is 40μm, and compressive strength is >4000psi.
[0079] The cementitious material, active material, strength enhancing material, density regulating material, fluid loss reducing agent and dispersant were uniformly mixed according to the weight ratio in Table 4 to form dry powder, and a low-temperature, early-strength, low-density cement-based material 4# for deepwater cementing was obtained.
[0080] The cement slurry was prepared according to GB / T19139 standard with a water-cement ratio of 0.6, and the cement slurry system 4# was prepared by using low-temperature, early-strength, low-density cement-based material 4# for deep water cementing.
[0081] Example 5
[0082] As a preferred embodiment of the present invention, the specific composition of the low-temperature, early-strength, low-density cement-based material for deep-water cementing in this embodiment is shown in Table 5 below:
[0083] Table 5
[0084]
[0085]
[0086] In this embodiment, the cementitious material is a mixture of G-grade oil well cement and ultrafine silicate cement in a mass ratio of 7:3.
[0087] In this embodiment, the active material is a mixture of kaolin and microsilicon in a mass ratio of 1:1.
[0088] In this embodiment, the active component A, active component B and reinforcing component of the strength enhancing material are mixed in a mass ratio of 1:3:1.
[0089] In this embodiment, the density adjustment material is hollow glass microspheres with a density of 0.44-0.48 g / cm3 , median particle size is 40μm, and compressive strength is >4000psi.
[0090] The cementitious material, active material, strength enhancing material, density regulating material, fluid loss reducing agent and dispersant were uniformly mixed according to the weight ratio in Table 5 to form dry powder, and a low-temperature, early-strength, low-density cement-based material 5# for deepwater cementing was obtained.
[0091] The cement slurry was prepared according to GB / T19139 standard with a water-cement ratio of 0.6, and the cement slurry system 5# was prepared by using low-temperature, early-strength, low-density cement-based material 5# for deep water cementing.
[0092] Comparative Example 1
[0093] This comparative example is the same as Example 1 except that the cementitious material does not contain ultrafine silicate cement.
[0094] Comparative Example 2
[0095] This comparative example is the same as Example 1 except that it does not contain strength reinforcing material.
[0096] Comparative Example 3
[0097] This comparative example is the same as Example 1 except that the strength enhancing material is replaced by a commercially available early strength agent.
[0098] Test Case
[0099] Referring to the GB / T19139 oil well cement test method, the cementing cement slurry systems prepared in Comparative Examples 1 to 3 and Examples 1 to 5 were tested for engineering properties such as density, water loss, fluidity, anti-channeling coefficient (SPN value), thickening time, and compressive strength at different curing temperatures. The results are shown in Tables 6 and 7.
[0100] Table 6
[0101]
[0102] According to the data in Table 6, it can be concluded that the water loss, fluidity and thickening time of the cementing slurry systems prepared in Examples 1 to 5 can well meet the construction requirements, and the density of the slurry is in the range of 1.30 to 1.55 g / cm 3 Compared with Example 1, the thickening time of the cement slurry system in Comparative Examples 1 to 3 is greatly prolonged, and the anti-channeling ability of the slurry is greatly reduced.
[0103] Table 7
[0104]
[0105] From the data in Table 7, it can be seen that the compressive strength of the cementing slurry systems prepared in Examples 1 to 5 after curing for 24 hours at 10°C is greater than 3.5 MPa, which meets the requirements of cementing construction. The compressive strength of the cement paste formed by the cementing slurry systems in Comparative Examples 1 to 3 is much lower than that in Example 1, and the compressive strength is significantly reduced.
[0106] It can be seen from the above embodiments that the technical solution of the present invention does not affect the construction performance of cement slurry, and can significantly promote the early hydration process of cement, greatly improve the strength development rate of cement slurry, improve the early strength of cement stone, and is beneficial to prevent low-temperature shallow water and gas channeling, thereby improving cementing quality.
[0107] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical solutions of the present invention, rather than limiting them, and certainly not limiting the patent scope of the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In other words, any changes or modifications made to the main design concept and spirit of the present invention that have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention in other related technical fields is also included in the patent protection scope of the present invention.
Claims
1. A low-temperature, early-strength, low-density cement-based material for deep-water cementing, characterized in that: The following raw materials are included in weight percentage: Cementitious material: 54-70wt%; Active material: 20wt%; Strength enhancing material: 3-6wt%; Density adjusting material: 5-15wt%; Fluid loss reducer: 1-3wt%; Dispersant: 1-2 wt%; The cementitious material is a mixture of G-grade oil well cement and ultrafine silicate cement in a mass ratio of 7:3; the active material is a mixture of metakaolin and microsilica in a mass ratio of 1:
1.
2. The low-temperature, early-strength, low-density cement-based material for deepwater cementing according to claim 1, characterized in that: The SiO2 content of the metakaolin is 48-54wt%, the Al2O3 content is 40-45wt%, and the powder particle size is less than 600 meshes.
3. The low-temperature, early-strength, low-density cement-based material for deepwater cementing according to claim 1, characterized in that: The SiO2 content of the micro-silicon is 96wt% and the particle size is 0.05-0.30μm.
4. The low-temperature, early-strength, low-density cement-based material for deepwater cementing according to claim 1, characterized in that: The density adjusting material is hollow glass microspheres with a density of 0.44-0.48 g / cm 3 , median particle size is 40μm, and compressive strength is >4000psi.
5. The low-temperature, early-strength, low-density cement-based material for deepwater cementing according to claim 1, characterized in that: The strength enhancing material is prepared by mixing active component A, active component B and reinforcing component in a mass ratio of 1:3:1, and the preparation method is as follows: Sa1, mixing the active component A and the reinforcing component to obtain powder A; Sa2, the active component B is placed in a ball mill and ball milled at a speed of 500 rpm for 6 hours to obtain powder B; Sa3. Powder A and powder B are pneumatically mixed to obtain a strength-enhanced material.
6. The low-temperature, early-strength, low-density cement-based material for deepwater cementing according to claim 5, characterized in that: The active component A is prepared by mixing carbide slag, biomass slag and aerated concrete waste in a mass ratio of 5:4:1, and the preparation method is as follows: Sb1, carbide slag, biomass slag and aerated concrete waste were placed in a ball mill according to a mass ratio of 5:4:1, with a liquid-to-solid ratio of 1.0, and ball milled at a speed of 400 rpm for 72 hours to obtain slurry A; Sb2. Place slurry A in a sealed stirring tank, add 1 wt% of the solid mass of the dispersion stabilizer in slurry A and stir at 80° C. for 72 h to obtain slurry B; Sb3, placing slurry B in a centrifugal device for liquid-solid separation, drying the solid phase at the bottom of the liquid-solid separation into dry powder to obtain active component A; Preferably, the CaO content of the carbide slag is 65-70wt%, and the pH is 12-13; the SiO2 content of the biomass slag is ≥65wt%, the Al2O3 content is ≥15wt%, and the particle size is less than 325 mesh; the aerated concrete waste is composed of tobermorite, semi-crystalline CSH (I), CSH gel and silicon dioxide, and after crushing and grinding, the powder fineness is less than 600 mesh; the dispersion stabilizer is a mixture of ketone-aldehyde condensation product and microcrystalline cellulose.
7. The low-temperature, early-strength, low-density cement-based material for deepwater cementing according to claim 5, characterized in that: The active component B is prepared by mixing modified zirconium silicon slag, silicon manganese slag, phosphorus slag and alkaline slag in a mass ratio of 3:2:1:
1. The modified zirconium silicon slag is prepared by making slurry C from zirconium silicon slag, and the slurry C is subjected to solid-liquid separation after neutralization, water washing and impurity removal, and then high-temperature drying and grinding to obtain a product; Preferably, the SiO2 content of the modified zirconium silicon slag is ≥90wt%, the pH is neutral, and the powder particle size is less than 325 mesh; the powder particle size of the silicon manganese slag is less than 325 mesh, the SiO2 content is 35-40wt%, the Al2O3 content is 9-12wt%, the CaO content is 25-28wt%, and the MgO content is 6-11wt%; the SiO2 content of the phosphorus slag is 35-40wt%, and the CaO content is 42-48wt%; the CaCO3 content of the alkali slag is 40-45wt%, the CaSO4 content is 7-10wt%, and the CaCl2 content is 10-14wt%.
8. The low-temperature, early-strength, low-density cement-based material for deepwater cementing according to claim 5, characterized in that: The reinforcing component is formed by mixing lithium silicate and aluminum sulfate in a mass ratio of 1:2; preferably, the purity of the lithium silicate is greater than 98wt%, and the purity of the aluminum sulfate is greater than 98wt%.
9. The low-temperature, early-strength, low-density cement-based material for deepwater cementing according to claim 1, characterized in that: The fluid loss reducer is a 2-acrylamide-2-methylpropanesulfonic acid (AMPS) / acrylamide (AM) copolymer; and the dispersant is a sulfonated acetone formaldehyde condensate.
10. The method for preparing a low-temperature, early-strength, low-density cement-based material for deep-water cementing according to any one of claims 1 to 9, characterized in that: include: The cementitious material, active material, strength enhancing material, density regulating material, fluid loss reducing agent and dispersant are uniformly mixed according to respective weight ratios to form dry powder, thus obtaining a low-temperature, early-strength and low-density cement-based material for deepwater cementing.
Citation Information
Patent Citations
Deep-water low-temperature low-density early-strength cementing slurry for well cementation
CN101747880A
Low-temperature cementing slurry system and composition thereof
CN105462571A
A liquid colloid filling low-temperature well-cementing cement mortar system
CN106634899A
Preparation method of composite early strength agent and application of composite early strength agent in deepwater well cementation
CN113683336A
All-solid waste nano hydrated calcium silicate gel early strength agent as well as preparation method and application thereof
CN115385593A
Cited By
A low-density cement composition useful for low-temperature cementing
CN122685366A